Regulation of Circulatory Muscle-specific MicroRNA during 8 km Run - Yin, Xin; Cui, Shufang; Li, Xin; Li, Wei; Lu, Qiu ju; Jiang, Xiao hong; Wang, Hui; Chen, Xi; Ma, Ji zheng (International Journal of Sports Medicine, 2020)
Acute prolonged endurance running has been shown to alter muscle-specific circulating microRNA (miRNA) levels. Here, eighteen participants completed an 8 km run. We assessed the levels of hsa-miR-1–3p, -133a-3p, -133b, and -206 and their correlation with conventional biomarkers following exercise. Compared to before exercise (Pre), 8 km run significantly increased the lactate level immediately after exercise (0 h). Myoglobin (Mb) level increased at 0 h while creatine kinase (CK) level increased 24 h after exercise (24 h). The levels of creatine kinase MB isoenzyme (CK-MB) and cardiac troponin I (cTnI) were all elevated at 24 h and within the normal physiological range; The levels of hsa-miR-1–3p, -133a-3p, -133b significantly increased at 0 h but only hsa-miR-133a-3p still elevated at 24 h. Only hsa-miR-206 level decreased at 24 h; Additionally, the changes of hsa-miR-1–3p and hsa-miR-133a-3p were correlated with Mb at 24 h. These findings suggest that muscle-specific miRNA elevation in plasma is likely physiological and that these miRNA may be used as potential biomarkers for load monitoring in individuals.
Keywords: internal load; exercise; circulating microRNAs; autonomic nervous system; plasma